Social connections combat loneliness and promote wellbeing among college students coming out of the COVID-19 pandemic - Cipolletta, Sabrina; Ronconi, Lucia; Tomaino, Silvia Caterina Maria (Frontiers in Psychology, 2025)
IntroductionThe COVID-19 pandemic impacted young people's mental health but we still need to explore this impact in the long term. The aim of this study is to analyze college students' wellbeing and loneliness in relation to the impact of the COVID-19 pandemic, social support, and the frequency of activities carried out with others following the period of strictest restrictions.MethodsA total of 291 college students enrolled in an Italian University filled in an online questionnaire including measures of anxiety, depression, life satisfaction, loneliness, perceived social support, and the impact of COVID-19 on their quality of life.ResultsThe results showed that the greatest impact of the pandemic related to higher levels of loneliness, anxiety, depression and lower satisfaction with life. Conversely, greater social support and frequency of activities carried out with others were associated with lower levels of loneliness and depression, and higher satisfaction with life. Some differences related to gender and being a long-term international student.DiscussionThese results are important to inform interventions to support college students' wellbeing and foster social connections among them.